2014
DOI: 10.4236/ajmb.2014.43017
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction Detection of ASFV Infection in Nigerian Indigenous Pig

Abstract: This work investigated the presence of African Swine Fever Virus (ASFV) in Nigerian Indigenous Pig (NIP) using Polymerase Chain Reaction (PCR) screening method on the extracted DNA from the pig blood. NIP population selected from south western Nigeria were used for this study. ASFV infected blood samples collected from the University of Ibadan were used as positive control. Adiscrete and specific band was observed in both NIP and the infected samples show the presence of ASFV in NIP. The bands were of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Some of the NIPs that survived the ASF outbreak were still alive and identified by farmers during a field visit to Zing, Taraba State, for another research study in 2019. Previously, studies in Nigeria have observed tolerance of NIP to ASFV, sometimes with no clinical signs or reduced death rates during outbreaks (Oluwole & Omitogun, 2014). Studies in the Democratic Republic of Congo and Mozambique, reported indigenous pigs in endemic areas infected with the ASFV remained asymptomatic (Patrick et al, 2020Penrinth et al,2004Patrick et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Some of the NIPs that survived the ASF outbreak were still alive and identified by farmers during a field visit to Zing, Taraba State, for another research study in 2019. Previously, studies in Nigeria have observed tolerance of NIP to ASFV, sometimes with no clinical signs or reduced death rates during outbreaks (Oluwole & Omitogun, 2014). Studies in the Democratic Republic of Congo and Mozambique, reported indigenous pigs in endemic areas infected with the ASFV remained asymptomatic (Patrick et al, 2020Penrinth et al,2004Patrick et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The transmission of the disease, as it now occurs in sub-Saharan Africa, is through the African soft tick (Ornithodoros moubata porcinus) and Warthogs or domestic pigs. The transmission through the warthog and soft ticks does not occur in West Africa, although ASF virus has been detected from Warthog in Nigeria of West Africa [9] and also in local pigs in Nigeria [10]. The presence of soft ticks is also confirmed in Warthogs [7].…”
Section: Introductionmentioning
confidence: 92%
“…Blood samples were collected from the jugular vein of pure NIP (20), crossbreds (10) and Backcross [14] into 5 ml sterile EDTA bottles and brought into the laboratory for haematological analyses and DNA extraction for Polymerase Chain Reaction (PCR).…”
Section: Blood Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that some local breeds of domestic pigs in Africa are also resistant [8]. Oluwole and Omitogun [9] reported the presence of ASFV in Nigerian pigs while Adeoye and Adebambo [10] carried out an investigation on the ASF outbreak survivors in Nigeria, their offspring and F 2 showed reduced antibody levels against ASF from 100% to 18.79%. Palgrave et al [11] also reported the ability of the virus to survive in one species and killing other species in the same family where it is likely to be due to their genetic variations.…”
Section: Introductionmentioning
confidence: 99%